2019
DOI: 10.21276/ijcmr.2019.6.9.14
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Antimicrobial Resistance in Staphylococcus and Spectrum of Oral Oxazolidinone Linezolid in Multidrug Resistant Staphylococcus in a Tertiary Care Hospital

Abstract: Introduction: Staphylococcus species is an asymptomatic colonizer which has exhibited increasing resistance to various antimicrobial agents in the recent times. Although, the organism was naturally susceptible to all the antimicrobial agents, it has acquired multi drug resistance via various mechanisms. In view of rising prevalence antimicrobial resistance, this study was undertaken to study the prevalence of methicillin resistance and the emergence of linezolid resistance amongst the Staphylococcal isolates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Azhar et al 48 showed 34 % and the other conducted by Thool et al 53 reported 23.5 % prevalence of LRSA in pus as given in Table. 34,36,[43][44][45]48,49,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] It can be seen from the data that going through the countries (Geographical region), the majority of LRSA was from Europe and Asia. The data on Linezolid resistance in S. aureus and the cause of Linezolid resistance (if any) is not sufficiently reported among southeast Asian countries.…”
Section: Prevalence Of Lrsamentioning
confidence: 99%
“…Azhar et al 48 showed 34 % and the other conducted by Thool et al 53 reported 23.5 % prevalence of LRSA in pus as given in Table. 34,36,[43][44][45]48,49,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] It can be seen from the data that going through the countries (Geographical region), the majority of LRSA was from Europe and Asia. The data on Linezolid resistance in S. aureus and the cause of Linezolid resistance (if any) is not sufficiently reported among southeast Asian countries.…”
Section: Prevalence Of Lrsamentioning
confidence: 99%